A keratin-based microparticle for cell delivery. (January 2021) - Thompson, Marc; Giuffre, Aaron; McClenny, Claire; Van Dyke, Mark
Keratin-based biomaterials represent an attractive opportunity in the fields of wound healing and tissue regeneration, not only for their chemical and physical properties, but also for their ability to act as a delivery system for a variety of payloads. Importantly, keratins are the only natural biomaterial that is not targeted by specific tissue turnover-related enzymes, giving it potential stability advantages and greater control over degradation after implantation. However, in-situ polymerization chemistry in some keratin systems are not compatible with cells, and incorporation within constructs such as hydrogels may lead to hypoxia and cell death. To address these challenges, we envisioned a pre-formed keratin microparticle on which cells could be seeded, while other payloads (e.g. drugs, growth factors or other biologic compounds) could be contained within, although studies investigating the potential partitioning between phases during emulsion polymerization would need to be conducted. This study employs well-established water-in-oil emulsion procedures as well as a suspension culture method to load keratin-based microparticles with bone marrow-derived mesenchymal stem cells. Fabricated microparticles were characterized for size, porosity and surface structure and further analyzed to investigate their ability to form gels upon hydration. The suspension culture technique was validated based on the ability for loaded cells to maintain their viability and express actin and vinculin proteins, which are key indicators of cell attachment and growth. Maintenance of expression of markers associated with cell plasticity was also investigated. As a comparative model, a collagen-coated microparticle (Sigma) of similar size was used. Results showed that an oxidized form of keratin ("keratose" or "KOS") formed unique microparticle structures of various size that appeared to contain a fibrous sub-structure. Cell adhesion and viability was greater on keratin microparticles compared to collagen-coated microparticles, while marker expression was retained on both.